Adaptive Protection Scheme Using Optimal Coordination of Directional Overcurrent Relays for Active Distribution Networks - Omar Muhammed Neda (Universitas Ahmad Dahlan, 2026)
Directional overcurrent relays (DOCRs) are widely used for the protection of distribution and sub-transmission systems due to their simplicity and cost-effectiveness. Proper coordination of these relays is essential to ensure selectivity, reliability, and fast fault clearance. However, due to the complex and nonlinear nature of modern power systems with high-level constraints, achieving optimal coordination is challenging. Traditional protection schemes relying on fixed relay settings often fail under dynamic operating conditions, leading to increased relay operating times, coordination violations, and protection blind zones. This paper develops an optimization-based DOCR coordination framework to minimize total inverse relay operating time while preserving coordination constraints, including predefined Coordination Time Intervals (CTIs) between primary and backup relays. Two strategies are proposed: a combined method, applying a single relay setting group for all network configurations, and an adaptive method, generating specific relay setting groups for each configuration or cluster. The adaptive method also incorporates relay characteristic curve tuning, allowing each DOCR to select the most suitable inverse-time characteristic. Both strategies are implemented using a Genetic Algorithm (GA) and tested on IEEE 8-bus system. Simulation results show that the adaptive method significantly outperforms the combined strategy. In the IEEE 8-bus system, total operating time is reduced from 56.7742 s to 13.0026 s (≈81.7%). However, its practical deployment may require reliable communication and configuration detection. These results confirm that the GA-based adaptive DOCR strategy provides faster, more selective, and reliable protection, making it highly suitable for modern active distribution networks.